Ethical Dimensions of AI Integration in Healthcare: Balancing Innovation with Social Responsibility - Siva Teja Reddy Kandula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the multifaceted implications of artificial intelligence integration within healthcare systems, exploring the technological foundations and the ethical considerations that shape its implementation. The article analyzes how cloud-based machine learning frameworks revolutionize clinical practice through enhanced diagnostic capabilities and expanded care access while introducing complex challenges related to patient privacy, algorithmic fairness, and digital equity. The discussion navigates the tension between technological advancement and ethical responsibility, proposing that explainable AI techniques and robust governance frameworks are essential for building trustworthy systems. The article illustrates how responsible AI architecture can address disparities in healthcare delivery while respecting patient autonomy by examining case studies in radiological analysis and telehealth applications. The article concludes that a holistic approach—prioritizing transparent design, continuous monitoring, and inclusive deployment strategies—is imperative for realizing AI’s potential to transform healthcare while upholding social justice and maintaining public trust in medical institutions.